Mass media as actors of world politics - V. V. Fokina (Vestnik MGIMO-Universiteta)
The article is devoted to the questions about mass media as non-governmental actors of world politics. The author notes the main activities of mass media in world politics, researches the state information policy, models of the relations of the state with mass media. The role of political censorship and propaganda in interaction with the international public opinion is considered especially.